ANALISIS MANAJEMEN RISIKO KEAMANAN SISTEM INFORMASI UJIAN CBT ONLINE PADA INSTANSI XYZ MENGGUNAKAN METODE NIST SP 800-30 - Siti Khusnul Khotimah (2022)
The rapid development of information and communication technology has resulted in many changes, especially in the field of education. This change was found in exam activities that were previously carried out manually, now using the CBT Online exam. This CBT Online exam information system is used by XYZ Agency to administer the national exam. In its application, the CBT Online exam will certainly experience obstacles in the form of threats and vulnerabilities that will hinder the process of implementing the exam. Therefore, this study was conducted to analyze risk management on information system security for the CBT Online exam using the NIST SP 800-30 method. The results of the analysis show that there is one level high risk risk transfer recommendation. Three levels of risk CBT exam information system online with recommendations for risk reduction, Bandwidth with recommendations for risk acceptance, and networks with recommendations for risk acceptance. Four level , namely computers, databases, network and communication equipment, and IT staff implementing the online CBT exam are given risk acceptance. In addition to these recommendations, to overcome problems in sustainable risk management, it is possible to develop a security risk assessment system for the CBT Online exam information system.